2021
DOI: 10.3390/foods10071510
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Functional Properties of Dietary Fibre Concentrates from Winemaking By-Products: Skins, Stems and Lees

Abstract: The objective of this study was to evaluate, from a technological and nutritional point of view, the chemical composition and functional properties of the industrial winemaking by-products, namely skins, stems and lees. The chemical and physical characteristics, as well as the functional properties (fat and water retention and swelling capacity, antioxidant capacity, and their prebiotic effect), of the dietary fibre of these by-products were studied. The results showed that the skins, stems, and lees are rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 76 publications
(80 reference statements)
4
19
0
Order By: Relevance
“…Glucose levels in tomato and pomegranate skins were significantly higher than those in grape and broccoli stems. This glucose may come from non-pectic polysaccharides or be a remnant of soluble sugars that were not completely removed during the extraction procedure, and other sugars identified in other studies coincide, although in different amounts, with those found in our study [ 14 , 32 , 33 , 34 ].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Glucose levels in tomato and pomegranate skins were significantly higher than those in grape and broccoli stems. This glucose may come from non-pectic polysaccharides or be a remnant of soluble sugars that were not completely removed during the extraction procedure, and other sugars identified in other studies coincide, although in different amounts, with those found in our study [ 14 , 32 , 33 , 34 ].…”
Section: Resultssupporting
confidence: 85%
“…Pomegranate peel was described with a lower amount of pectins, between 377 and 755 mg/g uronic acids [ 33 ]. Lower amounts of pectins were also found in grape and broccoli stems, ranging from 31.09 mg/g in grape stems [ 14 ] to 159.5 mg/g in broccoli stems [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lees are a residue formed during the ageing process of Cava (Spanish sparkling wine) and consist, mostly, of dead microorganisms (generally Saccharomyces cerevisiae ), tartaric acid, and other adsorbed compounds [ 15 , 16 ]. They are rich in antioxidant compounds [ 16 , 17 ] as well as dietary fiber from the yeast cell wall that is composed of mannoproteins and branched β-glucans [ 18 , 19 ]. Nowadays, Cava lees are produced at an amount of 300 tons per year, representing 25% of the waste generated by the wine industry [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, Cava lees are produced at an amount of 300 tons per year, representing 25% of the waste generated by the wine industry [ 17 ]. Although some studies have reported that wine lees could acquire an added value due to their composition [ 18 , 20 , 21 , 22 , 23 ], they are actually destined for distillation. Moreover, there is an increasing tendency in the food industry towards reducing food waste and re-valorizing by- and co-products to contribute to a circular economy and sustainable food production [ 10 , 13 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%